The Kinsip of Mandaresee and Javanese in Wonomulyo District (Study Linguistic Historical Comparative) (2023)
The purpose of this article is to find out the language kinship between Mandarese and Javanese and also to calculate the length of time of separation between the two languages. This article uses a quantitative descriptive research procedure. The instrument used is a gloss list of 200 vocabularies developed by Morrish Swadesh. The data collection techniques used were interviews with informants, recording, and recording. The data collected from both languages were analyzed using Comparative Historical Linguistics with lexicostatistic and glotochronology analysis techniques. The research results were divided into two, namely: (1) The results of the lexicostatistic analysis showed that the level of kinship between Mandarese and Javanese was 21%, which means that Mandar and Javanese are descended from the Malayo-West Polynesian language family. (2) The results of the glotochronology analysis show that the separation between Mandarese and Javanese occurred for 1,082 years which occurred approximately between 4,240 and 3,158, which means that they are classified as descendants of a language family.